2022
DOI: 10.1007/s40262-022-01183-6
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Safety of Tucatinib in Volunteers with Hepatic Impairment

Abstract: Background and Objective Tucatinib, a highly selective tyrosine kinase inhibitor of the human epidermal growth factor receptor 2 (HER2) approved for HER2-positive metastatic breast cancer, is cleared by hepatic metabolism and subsequent biliary excretion. Liver disease can alter drug disposition and pharmacokinetics (PK). The objective of this study is to characterize PK and safety of tucatinib in volunteers with hepatic impairment. Methods This Phase 1 study compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Our data indicated that HCC1569HER3KO cells expressing HER3 WT/V104L had reduced cell proliferation and viability in response to increasing concentration of tucatinib (1.5 −5.0 µM) (Figure 2D,E and Figure ). Since tucatinib has a shorter half‐life (~8.67 h), 36 HCC1569HER3KO cells stably expressing HER3 WT or HER3 V104L were subjected to 1.5 µM tucatinib for 1–4 h and our immunoblotting data showed that 1.5 µM tucatinib suppressed HER2 activation in both HCC1569HER3KO expressing HER3 WT/V104L in time dependent manner (Figure 2F and Figure ). We used another pan‐HER inhibitor, afatinib on HCC1569HER3KO cells expressing HER3‐WT and HER3‐V104L.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our data indicated that HCC1569HER3KO cells expressing HER3 WT/V104L had reduced cell proliferation and viability in response to increasing concentration of tucatinib (1.5 −5.0 µM) (Figure 2D,E and Figure ). Since tucatinib has a shorter half‐life (~8.67 h), 36 HCC1569HER3KO cells stably expressing HER3 WT or HER3 V104L were subjected to 1.5 µM tucatinib for 1–4 h and our immunoblotting data showed that 1.5 µM tucatinib suppressed HER2 activation in both HCC1569HER3KO expressing HER3 WT/V104L in time dependent manner (Figure 2F and Figure ). We used another pan‐HER inhibitor, afatinib on HCC1569HER3KO cells expressing HER3‐WT and HER3‐V104L.…”
Section: Resultsmentioning
confidence: 93%
“…Figure S3C). Since tucatinib has a shorter half-life (~8.67 h),36 HCC1569HER3KO cells stably expressing HER3 WT or HER3 V104L were subjected to 1.5 µM tucatinib for 1-4 h and our immunoblotting data showed that 1.5 µM tucatinib suppressed HER2 activation in both HCC1569HER3KO expressing HER3 WT/V104L in time dependent manner (Figure2Fand FigureS3D).We used another pan-HER inhibitor, afatinib on HCC1569HER3-KO cells expressing HER3-WT and HER3-V104L. Our data showed that afatinib in a dose dependent manner (0.25−1 µM) inhibited both HER3-WT and HER3-V104L cell proliferation (FigureS4A-C).…”
mentioning
confidence: 99%
“…2 Geometric mean oral clearance after a single 300 mg tablet dose was ~ 109 L/h. 3 Due to the moderate-high clearance and low-moderate distribution volume of tucatinib, the elimination half-life in human was ~ 9 hours, 3 requiring b.i.d. administration to maintain drug levels.…”
Section: How Might This Change Clinical Pharma-cology or Translationa...mentioning
confidence: 99%
“…Tucatinib fraction absorbed was assumed to be 50% based on mass‐balance data 2 . Geometric mean oral clearance after a single 300 mg tablet dose was ~ 109 L/h 3 . Due to the moderate‐high clearance and low‐moderate distribution volume of tucatinib, the elimination half‐life in human was ~ 9 hours, 3 requiring b.i.d.…”
mentioning
confidence: 99%